Clinical features of endometriosis: a review of literature - Thatikonda, Rajashree; Palve, Tushar; Shaikh, Soheil; Bulchandnani, Priya; Kulkarni, Sejal; Devnikar, Komal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Aim: To know the clinical features and prevalence of infertility in endometriosis. Objectives: 1. to discuss clinical features of endometriosis 2. to know the prevalence of infertility in endometriosis Material and methods: Background: The study shows the clinical features of endometriosis, common laparoscopic findings of endometriosis, and incidence in a particular age group. Objectives of current study were to discuss the clinical features of endometriosis and to know the prevalence of infertility in endometriosis Methods: Cases of infertility, chronic pelvic pain, dysmenorrhoea, and laparoscopically diagnosed endometriosis were considered for this study. Results: Endometriosis is a disease in which the endometrium (the tissue that lines the inside of the uterus or womb) is present outside the uterus. Endometriosis most commonly occurs in the lower abdomen or pelvis, but it can appear anywhere in the body. Symptoms of endometriosis include lower abdominal pain, dysmenorrhoea, dyspareunia, and infertility. Conclusions: This study show typical clinical features and prevalence of infertility in patients with endometriosis in a tertiary care centre. Cases of infertility, chronic pelvic pain, dysmenorrhoea, and laparoscopically diagnosed endometriosis were considered for this study. Results and conclusion: Endometriosis is a disease in which the endometrium (the tissue that lines the inside of the uterus or womb) is present outside of the uterus. Endometriosis most commonly occurs in the lower abdomen or pelvis, but it can appear anywhere in the body. Symptoms of endometriosis include lower abdominal pain, dysmenorrhoea, dyspareunia, and infertility. This study is to know the common clinical features and prevalence of infertility in patients with endometriosis in a tertiary care centre.